Pengembangan Desain Batik Limbah Grajen di Bulakan Sukoharjo, Jawa Tengah - Fify Fitriani; Setyawan . (JURNAL RUPA, 2019)
Grajen (sawdust) Batik is batik made using a natural dye that comes from the waste of wood cutting that is in the form of timber powder (which is called Grajen in the Javanese Language). Grajen Batik is developed in Bulakan Sukoharjo Java Tengah. Batik craftsmen in Bulakan region have dozens of years to pursue the process of batik and they have a specialization in the batik motif of parang, kawung, kopi pecah and tirtotejo. Batik motifs that evolve in Bulakan do not portray the typical characteristics of the Bulakan region, because batik craftsmen in Bulakan for tens of years have only been making the development of motifs. Therefore it is necessary to develop batik which has typical characteristics of the neighbourhood where the craftsmen live in order to distinguish with batik existing in other regions. This research used the method of qualitative research with an approach to the design and ethnography, which aims for the design to be laid out as a product of the culture in which the existence of batik does not appear on its own, but there is the context of socio-culture as well as underlying history.